1989
DOI: 10.1111/j.1365-277x.1989.tb00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nutritional intake using dietary records with estimated weights

Abstract: We report here three small studies designed to investigate aspects of the use of unweighed dietary records based on detailed food descriptions with portion sizes estimated using household measures and standardised photographs. Firstly, a study was carried out to compare nutritional intake calculated from data collected by a 7‐d weighed record with nutritional intake calculated from a 7‐d estimated record completed by the same individual. Secondly, to measure the repeatability of a 7‐d estimated record, two est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 6 publications
1
34
1
Order By: Relevance
“…In other studies 23 -25,28 fewer differences were found and in one study 26 most nutrients were significantly different. The associations between the energy and nutrient intake estimates were higher on average in this study than those reported by Bingham et al 25 , Edington et al 23 and Bonifacj et al 26 , but lower than those reported by Bransby et al 22 , Karvetti and Knuts 27 and Crawford et al 28 . The only other studies presenting the distribution in quartiles of energy and nutrient intakes were those of Bingham et al 25 and Bonifacj et al 26 .…”
Section: Discussioncontrasting
confidence: 68%
“…In other studies 23 -25,28 fewer differences were found and in one study 26 most nutrients were significantly different. The associations between the energy and nutrient intake estimates were higher on average in this study than those reported by Bingham et al 25 , Edington et al 23 and Bonifacj et al 26 , but lower than those reported by Bransby et al 22 , Karvetti and Knuts 27 and Crawford et al 28 . The only other studies presenting the distribution in quartiles of energy and nutrient intakes were those of Bingham et al 25 and Bonifacj et al 26 .…”
Section: Discussioncontrasting
confidence: 68%
“…Subjects were given detailed instructions on how to complete accurately a validated, 12 d semiquantitative food record (Edington et al, 1988) on either 12 consecutive days or from three sequences of 4 consecutive days followed by a few days rest but overall including 3 ± 4 weekend days. The importance of the 12 d recording period being representative of their normal eating patterns was explained to subjects.…”
Section: Methodsmentioning
confidence: 99%
“…This method of dietary assessment has been shown by Edington et al (1988) to have similar reliability to weighed food records, which are considered the most precise method. As calculated by Bingham (1987), 12 days are required to record individual, long-term iron intake within 10% of the mean.…”
Section: Nutrient and Iron Status Of Vegetarians Ak Wilson And Mj Ballmentioning
confidence: 97%
“…When foods were eaten out of the home, self-reported estimations using approximate household measures or photographs of servings (Eddington et al, 1989) were used and later converted to weights. Foodcodes and weights were entered twice onto spreadsheets (Excel v.4.0, Microsoft Corporation, Redmond, USA) and compared and corrected (with reference to the diaries) for differences.…”
Section: Methodsmentioning
confidence: 99%